Penguatan identitas negara: Upaya menanamkan nasionalisme pada generasi muda di era globalisasi - Nadhifah, Dina Wahda (Maliki Interdisciplinary Journal, 2026)
State identity is the national identity that distinguishes one country from another. In the era of globalization, technological developments and the entry of foreign cultures have influenced the lives of the younger generation. These influences can reduce the sense of nationalism if they are not balanced with a proper understanding of national identity. This study aims to determine the importance of strengthening state identity among the younger generation amid globalization. The research method used is qualitative with a literature study approach. Data were obtained from journals, books, and scientific repositories related to state identity. The results show that strengthening state identity can be carried out through civic education, the implementation of Pancasila values, the preservation of local culture, and the wise use of social media. By strengthening state identity, the younger generation is expected to maintain nationalism, preserve national unity, and protect Indonesian culture in the era of globalization.